2015
DOI: 10.3791/52448
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Comparing Nutrients in Beebread Made by Africanized and European Honey Bees and the Effects on Hemolymph Protein Titers

Abstract: Honey bees obtain nutrients from pollen they collect and store in the hive as beebread. We developed methods to control the pollen source that bees collect and convert to beebread by placing colonies in a specially constructed enclosed flight area. Methods were developed to analyze the protein and amino acid composition of the pollen and beebread. We also describe how consumption of the beebread was measured and methods used to determine adult worker bee hemolymph protein titers after feeding on beebread for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Flavonoids are minor compounds, but of great importance in bee pollen and thus bee bread. These compounds influence the aspect of the pollen grain (pigmentation) and taste (astringency and bitter taste) [ 46 ]. The most common flavonoids founded in bee pollen are the flavones and flavonols which occur almost exclusively as glycosides.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are minor compounds, but of great importance in bee pollen and thus bee bread. These compounds influence the aspect of the pollen grain (pigmentation) and taste (astringency and bitter taste) [ 46 ]. The most common flavonoids founded in bee pollen are the flavones and flavonols which occur almost exclusively as glycosides.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research in social bees has demonstrated the link between specific beneficial microbial taxa and larval health (Vásquez & Olofsson, 2009; Degrandi‐Hoffman et al ., 2015; Steffan et al ., 2017b; Dharampal et al ., 2020). Although similar studies in solitary bees are scarce, previous work indicates that the microbiota within the nests of congeners, Osmia bicornis (Keller et al ., 2013) and Osmia cornuta (Lozo et al ., 2015), are distinctly different from those seen in honey bees.…”
Section: Discussionmentioning
confidence: 99%
“…Bees use plant raw materials from outside of the hive (nectar, pollen, and resins) to produce honey, bee pollen, beebread, and propolis. Honey is the main bee product, the energetic source for the bees, while bee pollen and beebread are important protein, amino acids, lipids, fatty acids, sugars, vitamins, and mineral sources for the bee family [ 1 ]. Plant resins have been used for centuries in folk medicine to treat different diseases, before discovering the antibiotics [ 2 ].…”
Section: Introductionmentioning
confidence: 99%